CPM 2. Synthesis, Characterization and Field Evaluation of Nano-Structured Follar Fertilizer in Irrigated Rice (Oryza sativa L.) (The Philippine Journal of Crop Science, 2018)
This research aimed to synthesize, characterize and evaluate the effectiveness of nano-structured foliar fertilizer (NSFF) on the growth and yield of irrigated rice. Nano silica was synthesized from rice hull and nano calcium oxide from chicken eggshells. A (2x6) factorial experiment using 0ppm and 1000 ppm paclobutrazol (Factor A) and six fertilizer combinations (Factor B); control, NSFF (FAA-nCa-nSi thrice), RRIF, RRIF+NSFF twice, RRIF+NSFF thrice, and RRIF+ Commercial K-Silicate thrice was conducted in the field arranged in RCBD. Characterization of nanosilica (nSi) and nano calcium oxide (nCaO) through SEM micrographs revealed that the synthesized nSi was less than 30 nm, while XRD analysis of revealed to have a broad peak at 2 = 210- 220 indicating that the synthesized silica nanoparticles is amorphous. SEM analysis of nCaO revealed that the shape of particles was semi hexagonal which confirmed its crystallinity through XRD analysis. Macro analysis of NSFF (FAA-nCa-nSi) revealed that it contains total N at 2.43%; total P2O5 at 0.31%; total K2O at 1,78% and total Ca at 2.42%. Nano-structured foliar fertilizer combined with RRIF improved plant height, number of tillers per hill,number of productive tillers over the RRIF-treated plants while grain yield and harvest index are at par with RRIF. Paclobutrazol application exhibited consistent effect of reducing the plant height, length of lower internodes and culm length. NSFF can be a good supplement to inorganic fertilizers which can promote synergistic effect with lowlands irrigated rice.